Is a short-stage protocol during an incremental exercise test reliable for heart rate variability threshold analysis? - Cruz, Carlos Janssen Gomes da (2019)
Aim: Heart rate variability threshold (HRVT) is a valid method to determine parasympathetic depression during an incremental exercise test (IET). However, HRVT is usually assessed using the last 60s of each 180s stage of an IET, resulting in longer and demotivating tests. This study aimed to evaluate the agreement of HRVT analysis adopting the first and second minute of R-R interval (iRR) segment comparatively to a standard third-minute segment obtained at each 3-min stage on IET. Methods: Seventeen young male subjects (22.2 ± 3.1 years; 23.4 ± 2.3 kg/m2) underwent IET on a cycle ergometer. HRVT was considered the load corresponding to the point of stabilization of the SD1 index (HRVTV), or the first load with SD1 value < 3ms (HRVT<3), both assessed by the 1st (HRVT1V, HRVT1<3), 2nd (HRVT2V, HRVT2<3) and standard 3rd (HRVT3V, HRVT3<3) 60s iRR segment analyzed at each stage of IET. Agreement and reliability were assessed by the Bland-Altman analysis and the intraclass correlation coefficient (ICC), respectively. Results: High reliability and non-significant bias were observed considering HRVT1V vs HRVT3V (ICC = 0.92; p = 0.18) or HRVT2V vs HRVT3V (ICC = 0.94; p = 0.99). However, lower reliability was observed for HRVT1<3 vs HRVT3<3 (ICC = 0.79; p = 0.75) and for HRVT2<3 vs HRVT3<3 (ICC = 0.91; p = 0.33). Conclusion: HRVT can be similarly assessed by the 1st, 2nd or 3rd 60 seconds iRR segment, mainly when assessed by a visual method.